Manajemen Gudang Di Era Industri 4.0: Tinjauan Literatur Dan Arah Penelitian Ke Masa Depan - zaldi zain; Arsad Farezan; Muhammad Ghufron; Siti Sahara (Jurnal Ilmiah Wahana Pendidikan, 2023)
Warehouse management is an important part of the supply chain and plays an important role in ensuring the availability of goods and business continuity. In the era of Industry 4.0, the use of technology in warehouse management is becoming increasingly important to increase efficiency and productivity. This study aims to conduct a literature review regarding the application of technology in warehouse management in the Industry 4.0 era and explore future research directions. The results of the literature review show that technologies such as AGV, RFID, WMS, VR, AR, blockchain, and robotics can provide many benefits in warehouse management, such as increasing operational efficiency, increasing accuracy, improving work safety, and optimizing the use of warehouse space. However, there are several challenges in implementing technology in warehouse management, such as high implementation costs, inadequate employee skills, data security challenges, and different system compatibility.